Comparing employment trajectories before and after first imprisonment in four Nordic Countries - Aaltonen, Mikko (The British journal of criminology, 2017)
Employment plays a crucial role in the re-entry process and in reducing recidivism among offenders released from prison. But at the same time, imprisonment is generally regarded as harmful to post-release employment prospects. Little is known, however, about whether or not offenders’ employment trajectories before and after imprisonment are similar across countries. As a first step towards filling this gap in research, this paper provides evidence on employment trajectories before and after imprisonment in four Nordic welfare states: Denmark, Finland, Norway and Sweden. Using data gathered from administrative records on incarcerated offenders, the analysis focuses on individuals imprisoned for the first time and who served a prison sentence less than one year in length. Results show that although employment trajectories develop in mostly similar ways before and after imprisonment across these countries, important differences exist.